A review of psychological symptoms and post-traumatic growth among adolescent and young adult survivors of childhood cancer. (March 2022) - Berkman, Amy M; Robert, Rhonda S; Roth, Michael; Askins, Martha A
The majority of childhood cancer patients survive well into adulthood, but remain at risk for psychological late effects that can impact overall health and quality of life. The current narrative review summarizes the literature on psychological late effects, including anxiety, depression, psychological distress, post-traumatic stress disorder, suicidality, psychoactive medication use, and post-traumatic growth in survivors of childhood cancers. While results were mixed, many studies demonstrated that psychological symptoms occurred at levels higher than would be expected in the general population. Treatment, environmental, and behavioral risk factors, as well as symptom onset and trajectory merit further investigation.